The Impact of Ukrainian Refugee Crisis on the Unemployment of most affected EU Countries - Maidanyk, Nikita (2024)
This thesis examines the economic impact of the Ukrainian refugee crisis on the most affected EU countries. Initially focusing on the unemployment rate, the study soon shifted to analyzing Gross Domestic Product per capita based on purchasing power parity (GDP per capita PPP) to capture a more comprehensive view of the economic impact. This shift was necessitated by the limitations of unemployment rates in fully reflecting the broader economic consequences. The research employs the Synthetic Control Method (SCM) to construct synthetic control units for the affected countries to isolate and measure the impact of the crisis. The results show that while initial analyzes using unemployment rates were inconclusive, the examination of GDP per capita PPP revealed an economic slowdown in countries such as Poland, Czechia, and Germany following the crisis. These findings indicate that the refugee influx has had an impact on the economic stability of most affected countries. The study emphasizes the necessity for adaptable EU economic policies to effectively manage large-scale refugee movements, thereby enhancing the understanding of economic resilience and policy efficiency.